2016
DOI: 10.1111/ejn.13382
|View full text |Cite
|
Sign up to set email alerts
|

A comparative transcriptomic analysis of astrocytes differentiation from human neural progenitor cells

Abstract: Astrocytes are a morphologically and functionally heterogeneous population of cells that play critical roles in neurodevelopment and in the regulation of central nervous system homeostasis. Studies of human astrocytes have been hampered by the lack of specific molecular markers and by the difficulties associated with purifying and culturing astrocytes from adult human brains. Human neural progenitor cells (NPCs) with self-renewal and multipotent properties represent an appealing model system to gain insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 97 publications
3
49
0
Order By: Relevance
“…Moreover, many NATs are expressed in the CNS where they have been shown to play fundamental roles in a variety of biological processes. For example, our previous work demonstrates that NAT dysregulation is associated with Alzheimer’s disease pathophysiology (Modarresi et al , 2011; Magistri et al , 2016), and in separate reports we have also revealed that NATs contribute to Parkinson’s disease, Autism, Fragile X mental retardation, seizures and metabolism (Scheele et al , 2007; Faghihi et al , 2010a; Pastori et al , 2014; Hsiao et al , 2016; Silva et al , 2016). Mechanistically, we and others have shown that NATs can mediate epigenetic modification of genes in cis , making them unexplored targets to achieve specific up-regulation of gene expression (Modarresi et al , 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, many NATs are expressed in the CNS where they have been shown to play fundamental roles in a variety of biological processes. For example, our previous work demonstrates that NAT dysregulation is associated with Alzheimer’s disease pathophysiology (Modarresi et al , 2011; Magistri et al , 2016), and in separate reports we have also revealed that NATs contribute to Parkinson’s disease, Autism, Fragile X mental retardation, seizures and metabolism (Scheele et al , 2007; Faghihi et al , 2010a; Pastori et al , 2014; Hsiao et al , 2016; Silva et al , 2016). Mechanistically, we and others have shown that NATs can mediate epigenetic modification of genes in cis , making them unexplored targets to achieve specific up-regulation of gene expression (Modarresi et al , 2012).…”
Section: Introductionmentioning
confidence: 76%
“…New isolation and culture protocols maintaining a non-reactive state of primary human and mouse astrocytes demonstrate the importance of xeno-free and supportive cultures (154,208,248). Additionally, by applying defined conditions hPSC derived astrocytes differentiating via a glia restricted progenitor (GRP) state demonstrate strong transcriptional changes after FBS exposure (20), which is also observed for primary GRP (155). However, withdrawal of FBS induced changes indicating a conversion back towards a non-reactive state (20).…”
Section: Reactive Response By Astrocytesmentioning
confidence: 93%
“…The morphology of isolated primary astrocyte is affected by in vitro culturing, which been demonstrated to be dependent on the application of fetal bovine serum (FBS). Defined medium or FBS containing conditions show significant differences on morphology, maintaining profound stellate morphology while inducing polygonal morphology, respectively (154,155). Protoplasmic astrocytes in vivo can lose their bushy morphology acquiring a reactive phenotype reducing SLC1A2 while increasing CD44 expression (121).…”
Section: Astrocyte Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of astrocyte-specific lncRNAs was done as already mentioned for neurons. Here we combined NPCs, Astrocytes and annotated lncRNAs RNAseq datasets [17]. We then extracted XH lncRNA expression, as already explained for neuronal differentiation.…”
Section: Lower Involvement Of Divergent Lncrnas During Astrocytic Difmentioning
confidence: 99%